The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1097/prs.0b013e3181b17b8f
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Skin Quality after Fat Grafting: Clinical Observation and an Animal Study

Abstract: This study shows that fat tissue grafting stimulates a neosynthesis of collagen fibers at the recipient site and makes the dermis thicker. However, the long-term effects remain undetermined and need further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
101
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(112 citation statements)
references
References 22 publications
3
101
0
8
Order By: Relevance
“…The mean percentage of scar improvement between before-and after-treatment quantitative assessments showed that autologous fat transfer is more effective in improving ice-pick scars and there were no significant differences in the total number of scars from fractional CO 2 laser for rolling and boxcar scars. Previous histologic and immunohistologic studies demonstrated a large difference in results between fat grafting and fractional ablative CO 2 laser for the treatment of acne scars, and favored fat grafting [35] . Histologic and immunohistologic experimental study compared biopsies taken from nude mice before and after fat graft, and showed an increased density of extracellular matrix surrounding the fatty tissue and between the fatty tissue and the dermis [32] .…”
Section: Discussionmentioning
confidence: 99%
“…The mean percentage of scar improvement between before-and after-treatment quantitative assessments showed that autologous fat transfer is more effective in improving ice-pick scars and there were no significant differences in the total number of scars from fractional CO 2 laser for rolling and boxcar scars. Previous histologic and immunohistologic studies demonstrated a large difference in results between fat grafting and fractional ablative CO 2 laser for the treatment of acne scars, and favored fat grafting [35] . Histologic and immunohistologic experimental study compared biopsies taken from nude mice before and after fat graft, and showed an increased density of extracellular matrix surrounding the fatty tissue and between the fatty tissue and the dermis [32] .…”
Section: Discussionmentioning
confidence: 99%
“…Face is an ideal recipient site with rich blood supply which acts as an optimal scaffold, yielding a high percentage take of transplanted adipose cells [11]. An article by Mojallal et al [19] examined the effects of human fat transfer in mice from a clinical and histologic level. The authors found that the transplanted fat stimulated a ''regenerative effect'' on the overlying skin resulting in increased pore diameter and overall elasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Fat grafting is the author's preference due to many reasons: the fat is abundant, the procedure is autologous, fat grafting is a cell transplant which has anti-inflammatory "anti-fibrotic" and "trophic" effects with a possibility of achieving better skin quality, and the results are natural [25][26][27] . In literature, there is no difference in clinical results regarding the donor site, the use of anesthetic agents, vasoconstrictors, negative pressure, harvested fat process methods (centrifugation, decanting, washing, etc.)…”
Section: Discussionmentioning
confidence: 99%